Leading small and mid-sized urban school districts - Sutherland, Ian E.; Sanzo, Karen; Scribner, Jay Paredes, 1963- (Bingley, U.K. : Emerald, 2015)
The majority of the research in the US public education system has been conducted in large urban areas that do not reflect the majority of urban systems. The categorization of the size of districts does not capture the organizational diversity and complexity of school systems, including at-risk students and other demographic variables. The implications are that policy, preparation, research and funding are adversely skewed by an overrepresentation of research in urban districts that do not reflect the majority. This edited collection explores the ways in which small to mid-sized school districts influence leadership preparation, leadership practice, and accountability and assessment. With contributions from respected specialists, the volume addresses topics such as coaching, poverty, leadership preparation programs, accountability and assessment, English Language Learners, district leadership, and organizational learning and trust.
Large and small urban school districts : empirical identification and comparison utilizing student population / Craig Hochbein, Kristin Harbour -- Leadership preparation in small and mid-sized urban school districts / Karen Sanzo, Jay Scribner -- Working conditions and retention of principals in small and mid-sized urban districts / Edward Fuller, Liz Hollingworth, Michelle Young -- Principals and teachers decision making power in small, medium, and large school districts / Jiangang Xia, Xingyuan Gao, Jianping Shen -- Teaching students in poverty in small and mid-sized urban school districts / Mark Lineburg, Brian Ratlif -- Leadership for English learners / Jessica Costa -- Engaging Latino parents in the middle : valuing, validating, and building upon what families already do / Anne Marie FitzGerald -- Instructional leadership for special education in small to mid-size urban school districts / Marsha Cale, Candace Delpino, Steve Myran -- Prekindergarten interventions and instructional leadership in small and mid-sized urban school districts / Raleta Summers, Ian Sutherland -- Executive coaching of school leaders in mid-sized urban school district : development of a model of effective practice / John Weathers, George White -- Educational leadership in medium and small urban districts serving the new mainstream / Martin Scanlan, Rebecca Lowenhaupt -- A look into the workings of data use in a mid-sized district / Jeffrey Wayman, Vincent Cho, Jo Beth Jimerson, Virginia Snodgrass Rangel.
Print version record
Keywords: Education; School districts -- United States -- Management; Educational leadership -- United States